2010
DOI: 10.1682/jrrd.2010.01.0010
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric hearing status of individuals with and without multiple sclerosis

Abstract: Abstract-The purpose of the present investigation was to determine whether differences exist in audiometric hearing status between individuals with and without multiple sclerosis (MS) and between individuals with relapsing-remitting MS (RRMS) and individuals with secondary progressive MS (SPMS). Forty-seven subjects with MS (26 with RRMS and 21 with SPMS) and forty-nine control subjects without MS completed both a comprehensive case-history questionnaire and a conventional hearing evaluation. Statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…While our auditory findings are in general accord with a number of case-control studies (e.g., Cohen & Rudge, 1984; Coelho et al, 2007), they contrast with those of several others (Simpkins, 1961; Dayal & Swisher, 1967; Lewis et al, 2010). With rare exception (e.g., Dayal & Swisher, 1967), one-to-one matching of the MS subjects to controls on the basis of sex and age was not performed in these studies, and most employed relatively small samples.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While our auditory findings are in general accord with a number of case-control studies (e.g., Cohen & Rudge, 1984; Coelho et al, 2007), they contrast with those of several others (Simpkins, 1961; Dayal & Swisher, 1967; Lewis et al, 2010). With rare exception (e.g., Dayal & Swisher, 1967), one-to-one matching of the MS subjects to controls on the basis of sex and age was not performed in these studies, and most employed relatively small samples.…”
Section: Discussionsupporting
confidence: 86%
“…With rare exception (e.g., Dayal & Swisher, 1967), one-to-one matching of the MS subjects to controls on the basis of sex and age was not performed in these studies, and most employed relatively small samples. Among the larger case-control studies was that of Lewis et al (2010). As noted in the introduction, these investigators reported that the pure-tone thresholds of 47 MS patients – mostly veterans – were, on average, higher than those of 49 controls, with a greater deficit occurring in patients with secondary progressive MS (SP) than in normal controls or in patients with relapsing-remitting MS (RR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that patients with MS also experience more hearing loss than age-matched control subjects. [1][2][3] Some patients with MS exhibit deficits processing auditory stimuli, including speech in a background of noise. 4,5 Even patients with MS with hearing in the normal range sometimes present with subjective complaints of hearing problems.…”
Section: Sensory Symptoms Commonly Associatedmentioning
confidence: 99%
“…Thus, chronic SNHL seems to be common in patients with multiple sclerosis. 2,3 In addition, sudden SNHL has been described in several case reports, and is considered an important presentation of multiple sclerosis. [4][5][6][7] Herein, we describe a patient whose hearing was successfully restored by cochlear implantation even though his brainstem was affected by several multiple sclerosis lesions.…”
Section: Introductionmentioning
confidence: 99%